121k views
3 votes
Instructions:Drag the tiles to the correct boxes to complete the pairs. Match each polynomial function with one of its factors. Tiles f(x) = x3 − 3x2 − 13x + 15 f(x) = x4 + 3x3 − 8x2 + 5x − 25 f(x) = x3 − 2x2 − x + 2 f(x) = -x3 + 13x − 12 Pairs x − 2 arrowBoth x + 3 arrowBoth x + 4 arrowBoth x + 5 arrowBoth NextReset

User Muhd
by
6.8k points

2 Answers

5 votes

Answer: x + 3 is factor of
x^3-3x^2-13x+15,

x + 5 is factor of
x^4 + 3x^3 - 8x^2 + 5x - 25,

x - 2 is factor of
x^3 - 2x^2 - x + 2

And, x + 4 is factor
-x^3 + 13x - 12

Explanation:

Since if for a polynomial f(x), x-a is a factor then f(a)=0, ( because x=a is the zero of the polynomial)

Here, for
x^3-3x^2-13x+15,

If x=-3 then
x^3-3x^2-13x+15= -3^3-3(-3)^2-13* -3+15 =0

Therefore x-3 is the factor of
x^3-3x^2-13x+15.

At x=-5
x^4 + 3x^3 - 8x^2 + 5x - 25 is equal to zero.

Therefore, x+5 is the factor of
x^4 + 3x^3 - 8x^2 + 5x - 25.

At x=2
x^3 - 2x^2 - x + 2 is equal to zero.

Therefore, x-2 is the factor of
x^3 - 2x^2 - x + 2.

At x=-4
-x^3 + 13x - 12 is equal to zero.

Therefore, x+4 is the factor of
-x^3 + 13x - 12.

User Borko Kovacev
by
5.8k points
2 votes
We have the following functions:
f (x) = x3 - 3x2 - 13x + 15
f (x) = x4 + 3x3 - 8x2 + 5x - 25
f (x) = x3 - 2x2 - x + 2
f (x) = -x3 + 13x - 12
Factoring we have:
f (x) = x3 - 3x2 - 13x + 15 -------> x + 3
f (x) = x4 + 3x3 - 8x2 + 5x - 25 -> x + 5
f (x) = x3 - 2x2 - x + 2 ------------> x - 2
f (x) = -x3 + 13x - 12 -------------> x + 4
User Kelso Sharp
by
6.1k points